2010
DOI: 10.1037/a0015908
|View full text |Cite
|
Sign up to set email alerts
|

The relations of temperamental effortful control and anger/frustration to Chinese children's academic achievement and social adjustment: A longitudinal study.

Abstract: The prospective relations of temperamental effortful control and anger/frustration to Chinese children's (N ϭ 425, age range ϭ 6.6-9.1 years) academic achievement (grade point average, or GPA) and social adjustment (externalizing problems and social competence) were examined in a 2-wave (3.8 years apart) longitudinal study. Parents and teachers rated children's temperament, and parents, teachers, and/or peers rated children's externalizing problems and social competence. Effortful control positively predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
183
4
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(212 citation statements)
references
References 101 publications
11
183
4
11
Order By: Relevance
“…It has been suggested that high negative emotionality interferes with students' cognitive processes and lowers their motivation and engagement in classroom situations (Brand, Reimer, & Opwis, 2007;Zhou et al, 2010), because intense negative emotions can draw students' attention away from the task to threatening cues in the situation (Pekrun, 2005(Pekrun, , 2006. Empirical findings among middle school students have shown that negative emotionality is associated with low levels of academic performance and selfperceived competence (Guerin, Gottfried, Oliver, & Thomas, 1994;Gumora & Arsenio, 2002).…”
Section: Temperament In the School Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that high negative emotionality interferes with students' cognitive processes and lowers their motivation and engagement in classroom situations (Brand, Reimer, & Opwis, 2007;Zhou et al, 2010), because intense negative emotions can draw students' attention away from the task to threatening cues in the situation (Pekrun, 2005(Pekrun, , 2006. Empirical findings among middle school students have shown that negative emotionality is associated with low levels of academic performance and selfperceived competence (Guerin, Gottfried, Oliver, & Thomas, 1994;Gumora & Arsenio, 2002).…”
Section: Temperament In the School Contextmentioning
confidence: 99%
“…Temperament has been examined in relation to, for example, students' achievement, student-teacher interactions, problem behavior, and psychosocial functioning at school (e.g., Eisenberg et al, 2009;Nelson, Martin, Hodge, Havill, & Kamphaus, 1999;Valiente, Lemery-Chalfant, & Swanson, 2010;Zhou, Main, & Wang, 2010). For example, studies among kindergartners and elementary school students have found good self-regulation or high effortful control to be positively related to students' self-efficacy (Liew, McTigue, Barrois, & Hughes, 2008), academic competence (Liew et al, 2008;Valiente et al, 2010;Zhou et al, 2010), classroom participation (Valiente, Lemery-Chalfant, Swanson, & Reiser, 2008), school liking (Valiente, Lemery-Chalfant, & Castro, 2007), and work habits (Curby, Rudasill, Edwards, & Pérez-Edgar, 2011). Kindergarten and elementary school students' shyness or behavioral inhibition, TEMPERAMENT, AFFECTS, AND BEHAVIORS 6 on the other hand, has been shown to be negatively related to their academic engagement (Hughes & Coplan, 2010) and achievement (Hughes & Coplan, 2010;Valiente et al, 2010).…”
Section: Temperament In the School Contextmentioning
confidence: 99%
“…h ere is some evidence that the importance of self-regulation to school success generalizes to non-U.S. students. For instance, in a sample of Chinese primary schoolchildren, ef ortful control measured with parent and teacher ratings predicted report card grades, when baseline grades were controlled for (Zhou, Main, & Wang, 2010 ).…”
Section: High School Completionmentioning
confidence: 99%
“…The way students feel in school and the way they value school subjects and achievement are not only influenced by peers and teachers, but also by parents and other family members. The social-cognitive approach of achievement emotions (Pekrun, 2000) points out that values are transmitted by direct verbal information or by the behavior of one's significant others, and are adopted by students as a result (Eccles, 2007;Zhou, Main, & Wang, 2010). Parents and teachers are seen as significant "interpreters of reality" (Eccles et al, 1993, pp.…”
Section: Domain-specific Nature Of Academic and Achievement Emotionsmentioning
confidence: 99%